Fundamentals of drug delivery - Benson, Heather A. E.; Roberts, Michael S., 1949-; Williams, Adrian, 1963-; Liang, Xiaowen (Hoboken, NJ : Wiley, 2022)
'This book provides an insight into the fundamentals of drug delivery and the important processes in the development of controlled drug delivery systems. Part 1 introduces the concept of drug delivery and provides a perspective into the challenges, opportunities and fundamental processes involved in the development of controlled drug delivery systems. The 2nd part features a'top to bottom' critique of the common administration routes for controlled drug delivery, with each chapter discussing physiology pertient to each administration route and focusing on the barriers to drug delivery. In the last part, the emphasis i son particular challenges in controlled drug delivery and advanced delivery technologies -- including delivery systems for biologicals and equally enormous delivery challenges'--
Includes bibliographical references and index.
Keywords: Drug Delivery Systems; Drug Administration Routes